SOSIALISASI KONSEP 5S (5 R) PADA MASJID NURUL ILMI DI LINGKUNGAN KAMPUS UNIVERSITAS MUHAMMADIYAH A.R FACHRUDDIN - Suryo Sulistyo; Soerahman Soerahman; Sartono Sartono; Anni Rohimah; Yogi Priyo Istiyono; Rahmat Saputra; Abu Naim; Raden Hernadi (Jurnal Abdimas Bina Bangsa, 2023)
The Nurul Ilmi Mosque, which is located on the A.R Fachruddin Muhammadiyah University campus, should be used as a place to educate the public, especially regarding cleanliness, tidiness, comfort, which should have become a culture for Muslims. 5S is a very simple activity that can be done by everyone and is applicable. 5S or 5R is a method of arrangement and maintenance which is a principle popularized by Japan to create an orderly, neat and clean environmental culture so as to create an environment where activities are safe, comfortable, healthy, orderly, disciplined and responsible. Community service activities for the Socialization of the Application of the 5S (5 R) Concept at the Nurul Ilmi Mosque in the Muhammadiyah A.R Fachruddin University Campus Environment were carried out on April 5 2023 which was attended by lecturers and teaching staff and students of Muhammadiyah University A.R. Fachruddin, Implementation of the 5S program socialization is expected to form a personality that is disciplined and responsible for a clean and tidy environment